Evaluation of the results endonasal dacrocystorhinostomy in patients with DCR - Vaghela, Mukund; Patel, Alpesh; Patel, Vaibhav; Dhanani, Ankur (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Dacrocystitis refers to a series of clinical entities characterized by inflammation of lacrimal sac which leads to obstruction at the level of drainage of lacrimal system. Owing to the initial encouraging results and simplicity of the operation, it is decided that all symptomatic patients with lacrimal drainage obstruction would be treated initially by endoscopic endonasal dacrocystorhinostomy method, irrespective of the level of obstruction. Methods: A total 50 patients were included in the study over a period of 3-4 months. They were subjected to endonasal dacrocystorhinostomy and were evaluated for postoperative complications. Results: Very few complications were seen postoperatively suggesting that this newer technique may be useful. Conclusions: Endonasal dacrocystorhinostomy may prove better in coming years.